SAT0303 Discrepancies in the definition of inflammatory articular disease to determine the prevalence of psoriatic arthritis after applying caspar criteria in patients with cutaneous psoriasis. (23rd January 2014) - Fernandez-Sueiro, J.L.; Pinto Tasende, J.; Pértega Diaz, S.; González, E.; Fernandez Lopez, J.; Oreiro Villar, N.; de Toro, F.; Blanco, F.
Abstract : Background: To classify a patient with psoriasis arthritis (PsA) according to CASPAR criteria the patient must have and inflammatory articular disease (IAD) –joint, spine or entheseal- plus other criteria, however the lack of definition of entry criteria may difficult the correct classification of these patients. Objectives: To evaluate the differences in the prevalence of IAD (joint, spinal or entheseal) in patients with cutaneous psoriasis applying different definitions. To determine the prevalence of CASPAR criteria in these patients, according to CASPAR criteria, and to compare it with the clinical judgment of PsA. Methods: Descriptive and observational cross sectional study of 122 patients referred from the primary care with cutaneous psoriasis without arthritis. The prevalence of PsA along the 95% CI was determined according to CASPAR criteria using using different criteria for the definition of IAD. Peripheral arthritis: a) clinical criteria (TJC>0 or SJC>0 (78/76)), b) Ultrasound with power doppler (PDUS) carpal, MCP, PIP, MTsP, carpal tendons, hands and feet tendons, c) radiological (hands and/or feet erosions). Spine: a) clinical criteria (IBP (4/5) and/or nocturnal and VAS overall spinal pain past week >5, b) radiological (sacroiliitis grade II unilateral or higher). Entheseal: a) clinical criteria MASES plus lateral and medial epycondile, quadriceps tendon, proximal and distal patella, plantar aponeuroses. b) PDUS criteria lateral and medial epycondile, quadriceps tendon, proximal and distal patella, aquilles tendon plantar aponeuroses Results: Criteria for peripheral arthritis were met in the following: clinical criteria 12 (9, 8%), PDUS 16 (15%), erosions 20 (19%). Any of the 3 criteria 41 (41, 4%). None of the patients met the 3 criteria altogether. Criteria for spinal disease were met in the following: IBP 8 (12, 3%), VAS overall spinal pain past week >5, 22 (18%), sacroiliitis grade II unilateral or higher 17 (15, 5%). Radiological criteria plus one of the clinical criteria 5 (4, 4%). None of the patients met the 3 criteria altogether. Criteria for entheseal disease were met in the following: clinical 13 (10, 7%), PDUS 40 (32, 8%). Any of the 2 criteria 45 (36, 9%). 8 pacientes had both criteria. After applying CASPAR criteria 63 (61, 8%) patients (95% IC: 51, 8%>71, 7%) had criteria for (IAD) –joint, spine or entheseal-. Finally 33 patients (34, 7%) (95% IC: 24, 6%–44, 8%) met CASPAR criteria, 12 patients (9, 8%) (95%IC: 4, 1%–15, 5%) had PsA according to clinical judgment. Only 6 patients met both criteria (Kappa index=0, 140) Conclusions: The prevalence of PsA in patients with psoriasis, according to CASPAR criteria, varies depending on the definition of IAD. With several definitions of IAD, 34.7% of the patients met CASPAR criteria whereas only 9.8% of the patients met clinical criteria according to clinical judgment. These data suggest the need for defining criteria for IAD in PsA. Funded with a grant from: Instituto de Salud Carlos III, FIS PI080789 Disclosure of Interest: None Declared